BRAC Health Centres (CLINIC): current scenario and future prospects - Shatil, Tanvir; Hossain, Shamim (BRAC Research and Evaluation Division (RED), 2019)
OBJECTIVE This study was conducted to understand the current state of affairs in the upgraded BRAC Health Centres (now BRAC clinics) with in terms of infrastructure, operation, access, utilization of services and client satisfaction. METHODS A qualitative research was carried out in four BRAC clinics that have been selected out of the thirteen clinics that are currently in operation. Inventory, observation, exit-interviews, lOis (Indepth Interview), FGDs (Focus group Discussion) and informal discussions were used for collecting relevant information. FINDINGS All clinics were established in rented, multi-storied buildings that have been built for residential purposes. Therefore, they posed a problem in delivering health services. BRAC clinics provided maternal, neonatal and child healthcare that included services for common illnesses like fever, diarrhoea, TB and malaria, at a comparatively lower cost. Interestingly, the clinics were not oriented towards providing emergency care services (e.g. for road traffic accidents, for drowning, poisoning, first aid etc.) Routine diagnostic tests were available in the clinics. Prescribed medicine was mostly available in the clinic pharmacy at a nominal mark-up price. Waiting time for patients was also within reasonable limits. The doctors and staff were found to be modest and professional. BRAC HNPP's community health workers were found to play an important role in referring patients from the community to the clinics. Shortage of health professionals was a problem in all the clinics. Most of the patients were satisfied with the services. However, the common perception of the community was that the clinics were only for poor, pregnant women; that the clinic was mainly a maternal and child healthcare centre. Most of the community members did not know about the range of services provided at the clinics. The community members related the goodwill of BRAC to the BRAC clinics and hence perceived its services to be of good quality. CONCLUSION The study indicates that BRAC clinics are working in the community to meet the health challenges of community members. However, several barriers do exit. These include lack of community awareness regarding the activities and the range of services provided, shortage of skilled health professionals for the delivery of such services and poor infrastructure. However, clients were satisfied with the services and BRAC's goodwill has played a determinate role in / shaping the clinics' image in the community.